Keterampilan Bertanya Guru SMP dalam Pembelajaran Matematika - Nurdiansyah Nurdiansyah; Rahmah Johar; Saminan Saminan (Universitas Syiah Kuala, 2019)
Questioning skills is one of the basic skills taught are important to master teachers. Lack of good questioning skills possessed by teachers can lead students in an attention too. This study aimed to describe the questioning skills junior high school teacher in mathematics. This study used a qualitative approach with descriptive research. Subjects in this study are two mathematics teachers from two different schools: one teacher MTsN Matangglumpangdua and one teacher SMP N 5 Peusangan. Qualitative data analysis performed on both the teacher to see the questioning skills of teachers in learning. In general, teachers questioning skills include aspects of pausing, prompting and probing in mathematics has been done, but not all of the indicators on each aspect met for each meeting in both schools. In a study in MTsN during two meetings, at the prompting aspect is not done once the indicator solve the question into several sub-questions of the original question and the probing aspects of displacement indicators do not turn. Furthermore, in a study in junior high school for two meetings, on aspects prompting two indicators do not solve the question into several sub-questions of the original question and review (repeat) information previously provided.